Quality of Educational Platforms - Ahmed Elsheekh; Osama Mokhtar; Hesham Gameel (International Journal of Instructional Technology and Educational Studies)
What the world is witnessing today in terms of diseases and social distancing, in conjunction with the technological boom in communications and information technology, makes e-learning one of the most important priorities of governments at all levels. The real reality is the student explosion, as the number of secondary school students reached about (2 million) and vocational high school students (2 million), while the intermediate certificate also reached about (4 million) and the primary stage (8 million) in addition to students of institutes, higher institutes, and universities. This requires us to increase the number of educational facilities at a rate of three times what is currently available during the next ten years, as the number of primary school students today has tripled than it is now, and this makes education a chronic economic crisis during the third decade of the twenty-first century. This article presents a new proposal for how modern technology can be used to solve education problems in Egypt, in addition to achieving the goals of sustainable development and education. It also provides a solution to the problems of distance education.